1999
DOI: 10.1046/j.1469-0705.1999.14010042.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal assessment of Wharton's jelly in umbilical cords with single artery

Abstract: A reduction of Wharton's jelly is frequently present in cases of single umbilical artery. The increased perinatal morbidity and mortality observed in cases of single umbilical artery, even in the absence of congenital or chromosomal abnormalities, could be in part the consequence of a reduced amount of Wharton's jelly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 24 publications
(27 reference statements)
2
25
0
3
Order By: Relevance
“…Raio et al . demonstrated that the amount of Wharton's jelly is significantly lower in isolated SUA comparing with normal umbilical cords . Thus, it can be assumed that lacking the appropriate cushion, which prevents compression or bending of the umbilical cord, exposes the fetuses to be more vulnerable for blood‐flow disruption during labor.…”
Section: Discussionmentioning
confidence: 99%
“…Raio et al . demonstrated that the amount of Wharton's jelly is significantly lower in isolated SUA comparing with normal umbilical cords . Thus, it can be assumed that lacking the appropriate cushion, which prevents compression or bending of the umbilical cord, exposes the fetuses to be more vulnerable for blood‐flow disruption during labor.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the umbilical cord morphology and the Doppler blood flow characteristics of a number of fetal and extrafetal arteries in fetuses with SUA2–6. Persutte and Lenke7 and others8, 9 noted that the SUA is usually larger than are the arteries of normal umbilical cords. Raio et al 9 demonstrated that not only the artery but also the vein is larger in umbilical cords with SUA compared with those with three vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Raio and Colleagues (1999) reported an association between single umbilical artery and reduction of Wharton's jelly. 5 The water content of the umbilical cord has been studied in detail by Scott and Wilkinson (1978) Oedematous cords had a water content of 93.5% and wrinkled cords had 89.2% water. It was suggested that amount of Wharton's jelly or its water content goes on decreasing with advancing gestation.…”
Section: Discussionmentioning
confidence: 99%